Examining Determinants of Absenteeism among Blue Collar Employees in Petroleum Sector of Pakistan - ZEESHAN NOOR SIDDIQUI; KAMRAN NOOR SIDDIQUI; AYESHA NOOR SIDDIQUI (Journal of Business & Tourism, 2021)
The study focuses on the relationship between job satisfaction, job performance, and social / family compulsion and absenteeism in blue collar employees working in petroleum sector of Pakistan.150 blue collar employees from refineries and oil marketing companies were included in the survey and responded the questionnaire, encompassing all variables. Results prove hypothesis 1 whereas, hypothesis 2 could not be proven. Results will help Pakistani organization to reduce absence rate in their blue collar employees by understanding the social and family compulsions.